Effect of soil tillage intensity on the composition, physical and chemical properties of the second fraction of humic acids extracted from the typical black soil - Popirny, M. A.; Nikolov, O. T.; Skrylnik, E. V. (Biophysical Bulletin, 2016)
The purpose of this work lies in studying the composition, physical and chemical properties of the second fraction of the humic acid (HA2) extracted from the typical black soil, depending on the intensity of the soil tillage. Physical and chemical properties of HA2 have been studied by using ultraviolet (UV) spectroscopy, infrared (IR) spectroscopy and electron spin resonance spectroscopy (ESR). It has been demonstrated that increase of the tillage intensity of the typical black soil leads to decrease in the total carbon content and the HA2 content due to displacement of balance between the conjugated processes of humus synthesis and decay towards destruction. UV spectroscopy indicates intense absorption of humic acids in the near UV region, that corresponds to the donor-acceptor mechanisms π-π* electrons of double bonds. Maximum absorption has been observed for the HA2 isolated from the black soil tilled by plowing. Moreover, the highest content of oxygen-containing functional groups and low quantity of aliphatic structures has been observed in the same sample. It has been shown that the nature of paramagnetic centers of the HA2 represented by chelate paramagnetic Fe3+-complex formed by rearrangement π-electron system of double bonds, depending on the tillage intensity of the typical black soil. It has been found that plowing of the typical black soil enhances the number of paramagnetic centers in HA2.